PENYULUHAN DAN PELATIHAN PEMBUATAN SIRUP BUNGA TELANG KELOMPOK PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) DI DESA PANDEAN, KOTA MADIUN: COUNSELING AND TRAINING TO MAKE TELANG FLOWER SYRUP FOR FAMILY WELFARE EMPOWERMENT GROUP (PKK) IN PANDEAN VILLAGE, MADIUN CITY - Onny Priskila; Alfredo Aldo; Lily Sulistyowati (LPPM Universitas Abdurrab, 2025)
Introduction. Along with the issuance of Government Regulation Number 103 of 2014, Article 70 and 71, chapter on community empowerment, states that they can play an active role in efforts to develop traditional health. An active role can be implemented through community empowerment through family health empowerment (PKK) groups using family medicine gardens and skills. Butterfly pea syrup is one form of interesting and innovative processed innovation that can have economic value. Butterfly pea flowers have health benefits and are widely used as herbal medicine by the community. Method. The implementation of the activity is through counseling (lectures and discussions) and training. The activity was attended by 20 PKK mothers. The activity began with counseling on the ins and outs of butterfly pea flowers, then training in making butterfly pea flower syrup. Purpose. The purpose of this activity is for the community to understand how to make butterfly pea flower syrup so as to produce products with high economic value and explore the local potential of Pandean Village, Madiun City. Results. Community service activities were measured by giving questionnaires before and after the activity. The questionnaire given was 10 questions containing questions about butterfly pea flowers and how to make syrup. The results were analyzed using the Wilcoxon test with a sig result of 0.000, which showed a difference before and after the counseling. Conclusion. Counseling and training activities for making butterfly pea flower syrup have a positive impact. Counseling can increase understanding of all things butterfly pea flower, and training in making syrup can increase participants' skills.